Konsep Kekayaan Intelektual Komunal Atas Ekspresi Budaya Tradisional Seren Taun Kasepuhan Cisungsang Kabupaten Lebak - Inge Dwisvimiar (Universitas Serang Raya, 2022)
Indonesia is rich in various kinds of arts and culture. One of them is traditional culture which is a cultural heritage that has been passed down from generation to generation from the previous generation to the current generation. In this regard, legal protection of intellectual property is very important, especially regarding traditional cultural expressions. The research entitled Communal intellectual property for traditional cultural expressions (EBT) Seren Taun Kasepuhan Cisungsang aims to know, understand, and analyze the concept of communal intellectual property (IP) legal protection against Traditional Cultural Expressions (EBT) Seren Taun Kasepuhan Cisungsang in Lebak Regency and the factors which affects the legal protection of intellectual property against the Traditional Cultural Expression (EBT) of Seren Taun Kasepuhan Cisungsang in Lebak Regency. The research method uses qualitative descriptive analytical methods. Refers to law and regulations and references/literature that are carried out offline or online using primary, secondary and tertiary data as legal material. The results of the research on Communal Intellectual Property on Traditional Cultural Expressions of Seren Taun Kasepuhan Cisungsang in Lebak Regency have not been carried out properly and effectively. One of the contributing factors is that the Kasepuhan party is only aware of, but has not yet understood the importance of carrying out protection, inventory and documentation in the context of legal protection through collaboration between the government, Kasepuhan parties and related partie.